Araneid orb-weavers (Araneae, Araneidae) associated with riparian forests in southern Brazil: a new species, complementary descriptions and new records - Rodrigues, Everton Nei Lopes; de S. Mendonça, Jr., Milton (Zootaxa, 2011)
The Araneidae is a speciose family including web-spinning spiders that are very abundant in various terrestrial ecosystems. Sixty-five araneid species from 20 genera were collected during an inventory of riparian forests in southern Brazil. Among these were one new species, described here as Mangora piratini sp. nov. Also discovered were the previously unknown males of Alpaida citrina (Keyserling, 1893), A. octolobata Levi, 1988 and Testudinaria lemniscata (Simon, 1895), which are described here for the first time. Metazygia floresta Levi, 1995, Ocrepeira malleri Levi, 1993 and Testudinaria quadripunctata Taczanowski, 1879 are recorded for the first time for Rio Grande do Sul State, Brazil.